Macroeconomic Consequences of Tariffs - Furceri, Davide (IMF Working Papers; Working Paper ;, 2019)
We study the macroeconomic consequences of tariffs. We estimate impulse response functions from local projections using a panel of annual data that spans 151 countries over 1963-2014. We find that tariff increases lead, in the medium term, to economically and statistically significant declines in domestic output and productivity. Tariff increases also result in more unemployment, higher inequality, and real exchange rate appreciation, but only small effects on the trade balance. The effects on output and productivity tend to be magnified when tariffs rise during expansions, for advanced economies, and when tariffs go up, not down. Our results are robust to a large number of perturbations to our methodology, and we complement our analysis with industry-level data.